THE EFFECT OF RURAL DEVELOPMENT POLICY ON DOMESTIC VIOLENCE - Ćejvanović, Ferhat; Kovačević, Alma; Grgić, Zoran; Maksimović, Aleksandar; Miletić, Vesna (Economics of Agriculture, 2015)
Rural development policy deals with achieving goals for rural areas and a wide range of socioeconomic activities are included within it. This work intends to connect rural development policies with the occurrence of domestic violence in rural areas. The area of research is the territory of Tuzla Canton, which is, by defnition of OECD (less than 150 habitants/km2), a predominantly rural area. Domestic violence is a wide spread form of violence and a discrimination against women. Domestic violence includes all forms of violence occurring in the family, expanding the possibilities that perpetrators of violence and victims of violence may even be persons who do not live in the family but are related to family members, e.g. former partners, relatives, etc. Research results show that victims of domestic violence are in 90% of the cases women (wives, mothers, daughters, sisters, etc.) and that domestic violence is constantly increasing each following year. All forms of violence over women come stem from a principal discrimination towards women which results in coerce or use of force. For that reason, violence over women is a manifestation of a fundamentally unequal position of women and men, and it represents a form of discrimination against women. This paper uses data acquired from Federal Offce of Statistics of Federation of Bosnia and Herzegovina and statistical data from the Ministry of Internal Affairs of Tuzla Canton. On the basis of the gathered data, we employed the descriptive method, the method of analysis and synthesis, as well as the comparative method of analysis. The hypothesis of this paper was the assumption that "women in rural areas are more frequently victims of domestic violence than women living in urban areas".